Ethics education and accounting programmes in Ghana: does university ownership and affiliation status matter? - Simpson, S. N. Y.; Onumah, J. M.; Oppong-Nkrumah, A. (Springer International Publishing, 2016)
One very important remedy proposed for the wide-spread ethical failure of accountants in recent years is ethics education. Although ethics education has been variously explored in the literature, the nature of ethics education in accounting programmes and the factors that are associated with the integration of ethics education still remain largely unexplored, particularly in the context of developing countries and at university level of education. This study, therefore, ascertains the nature of ethics education and examines how two factors, namely the type of institution and the affiliation status of the institution, affect the structure and integration of ethics education in the accounting programmes of universities in Ghana. Drawing on primarily secondary data from twenty-seven (27) out of the thirty-four (34) universities in Ghana, results show that the content and structure employed in integrating ethics into accounting programmes are associated with the type of institution and the affiliation status of institutions.
Keywords: Ethics education; Accounting programme; Universities; Ghana